The development of the unified Baltic Sea Chart Datum 2000 (BSCD2000) height transformation grid: an unprecedented example of height system unification based on state-of-the-art marine geoid modelling - Joachim Schwabe; Sander Varbla; Jonas Ågren; Hergeir Teitsson; Artu Ellmann; Gunter Liebsch; René Forsberg; Gabriel Strykowski; Mirjam Bilker-Koivula; Ivars Liepiņš; Eimuntas Paršeliūnas; Kristian Keller; et al. (Journal of Geodesy, 2026)
The shallow Baltic Sea is a vital waterway with dense shipping traffic, requiring accurate and reliable nautical charts for safe navigation. Until recently, different realisations of the mean sea level were used in the paper charts of each country, sometimes even between harbours. This created obstacles for the digitalisation of ship navigation, including electronic nautical charts combined with satellite-based positioning. To resolve this, the Baltic Sea Hydrographic Commission decided in 2013 to introduce the Baltic Sea Chart Datum 2000 (BSCD2000) as a common height/depth reference system for the maritime sector in the Baltic Sea. The new reference level for all depth and water level information is strictly the quasigeoid, which is practically identical to the geoid at sea. The BSCD2000 is defined in accordance with the European reference systems: the European Terrestrial Reference System 1989 (ETRS89) for ellipsoidal coordinates and the European Vertical Reference System (EVRS) for physical heights. This enables the practical implementation of the zero level through a seamless height transformation grid with standard uncertainties of approximately 1–2 cm, which is harmonised with national coordinates, heights, and height reference surfaces. To the authors’ knowledge, this level of harmonisation is unprecedented in the maritime sector and exemplifies the value of the unification of height systems in geodesy. The paper outlines the foundations of the BSCD2000 and the approach to construct the BSCD2000 height transformation grid. While the computation of the gravimetric marine quasigeoid model is based on well-established methods, special focus is placed on practical harmonisation across national borders and along the coastline. To this end, a novel fitting and blending scheme based on distance maps was developed. Finally, comparison of the new gravimetric marine quasigeoid solution with a preliminary geometric marine geoid model based on SWOT altimetry data and hydrodynamic modelling confirmed good agreement within a few centimetres in most areas of the Baltic Sea.

From Discrete Gravity Survey Data to a High-resolution Gravity Field Representation in the Nordic-Baltic Region - Silja Märdla; Jonas Ågren; Gabriel Strykowski; Tõnis Oja; Artu Ellmann; René Forsberg; Mirjam Bilker-Koivula; Ove Omang; Eimuntas Paršeliūnas; Ivars Liepinš; Jānis Kaminskis (Marine Geodesy, 2017)